Figures of Speech in Mamluk Period - Ali Haydar (دراسات فی اللغه العربیه و آدابها, 2010)
Probably one of the most difficult tasks of scholars in range of figures of speech â a distinctive feacture characterizing the literary taste of this period . Opinions of experts in the area of figurative language differe concerning the number , names , and kinds of the figures . They also disagree over the role and significance of figures of speech in literary creation . Thisarticle is on attempt at accounting for these differences in opinion by comparing the most impotant works which have dealt with this area of literature . Some of the important topics in rhetoric and figurative language , which are in much disarray and difficult to tackle , have also been dealt with.